Development of personal biodosimeter of UV radiation based on vitamin D photosynthesis in nematic liquid crystal matrix - Dyadyusha, A.G.; Gvozdovsky, I.A.; Salkova, E.N.; Terenetskaya, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A new approach to the problem of personal UV biodosimeter is described. Nematic liquid crystal (LC-805) is converted into induced cholesteric phase using photosensitive chiral dopant of steroid biomolecules (7-dehydrocholesterol (provitamin D3) or 7-DHC-benzoate). Significant changes in optical characteristics of the LC films depending on the duration of UV exposure are observed as a result of UV initiated photoisomerizations that change helical twisting power of dopant molecules.